Bioactive luteoloside produced by Myroides odoratimimus, solvent-tolerant bacterium form the rhizosphere of Lonicera japonica. Issue 24 (17th December 2019) - Zhao, Y. X.; Wang, J. J.; Zhang, L.; Zhang, S.; Su, S. L.; Duan, J. A.; Yao, Z. Z.; Xu, S. K.
Abstract: Luteoloside (luteolin-7-O-glucoside), the biomarker of Lonicera japonica, was efficiently bio-synthetized from its cheaper precursor luteolin. The structure of luteoloside was characterized by LC-MS and NMR analyses. Compared to the significant inhibitory effect of luteolin on human hepatocyte cell line LO2 at high doses, luteoloside did not show obvious cytotoxic effects at any test dose. Moreover, luteoloside exhibited obvious promotive effects on human hepatocyte cells, suggesting a potential application in hepatoprotective therapies. Abstract :